Radical resection of the pancreas should not always be necessary in the surgical management of pancreatic solid pseudopapillary tumor in children - Divarcı, Emre; Dökümcü, Zafer; Çetingül, Nazan; Nart, Deniz; Yılmaz Barbet, Funda; Ergün, Orkan; Çelik, Ahmet (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Pancreatic solid pseudopapillary tumor (SPT) is a rare neoplasm in children. In this study, we aimed to present our surgical strategy based on minimal resection by enucleation or limited resection in localized pancreatic SPT. Materials and Methods: We retrospectively analyzed the medical records of children who underwent surgical resection between October 2011 and September 2016. Results: Five female patients with a median age of 15 years (range, 14-17 years) were operated. Tumors were located in the pancreatic head (n=4) or tail (n=1). The median greatest tumor diameter was 9 cm (range, 5-13 cm). All the patients were investigated with MRI before the resection to demonstrate the relationship between the tumor and the main pancreatic duct. Patients underwent enucleation (n=4) for head localization or local distal resection without splenectomy (n=1) at the pancreatic tail. At postoperative follow-up, major pancreatic leakage was observed in two patients and endoscopically treated. Surgical margins were negative in all patients. The median follow-up period was 44 months (range, 2-59 months) and no local recurrence or distant metastasis was observed in the postoperative period. Conclusion: An optimal surgical strategy is still controversial in pancreatic SPT in children. Radical resections such as pancreaticoduodenoctomy or distal pancreatectomy with splenectomy result in loss of pancreatic tissue for endocrine and exocrine functions. Minimal resections such as enucleation or limited pancreatic resection with negative surgical margins should be performed in selected patients with no invasion to the main pancreatic duct or adjacent organs.